Adaptations in the management of food and nutrition units during the Covid-19 pandemic (Research, Society and Development, 2021)
The objective of the study was to analyze the adaptations in the management of raw materials and good manufacturing practices during the Covid-19 pandemic in food and nutrition units (FNU) in two segments: commercial and industrial/corporate. The research was carried out with FNU managers from all over Brazil, through an online survey. It was identified that both segments were affected by the Covid-19 pandemic, with the commercial ones being the most entitled to provisional labor measure No. 936/2020. In addition, the commercial sector was the most affected by the waste of raw materials and the need to change suppliers during the pandemic. However, it was the industrial/corporate FNU that had more facilities in sanitary hygiene adjustments. There are many factors that have generated increasing failures in this segment, but the lack of previous knowledge and competent managerial practices greatly impacted the consequences during the pandemic.